Development Of A Formative Assessment Regime For Chinese-english Interpreter Training And Its Effects On Academic Achievement, Motivation, And Collaboration - Yan, Da (2024)
In China’s interpreter training programs, efforts to systematically develop and enact a formative assessment regime has been rarely documented in the extant body of scholarship. To gain a more comprehensive understanding of the applicability and impact of formative assessment regime, the present study adopted a multi-phase approach to explore the development, implementation, and learned lessons of a formative assessment regime in an interpreter training program at Xinyang Agriculture and Forestry University, a focal and representative institution of higher education in China. The researcher recruited 129 second-year interpreter learners, 7 lecturers, and 10 experts as participants in the study. Methodologically, an embedded experimental design was adhered to in the study to comprehensively include the pre-intervention, intervention, and post-intervention phases within a unified research framework. For the pre-, and post-intervention phases, the research used in-depth interview and focus group discussions to obtain viewpoints and understandings of trainees and trainers, and Delphi method for evaluative judgement of the experts. For the intervention phase, mixed-method quasi experimental approach was chosen to examine the effects of the developed formative assessment regime on the academic achievement, motivation, and collaboration in interpreter training, which were measured through a summative interpreting achievement test (SIAT), an interpreter learning motivation questionnaire (ILMQ), and naturalistic observation of classroom conversations respectively.